TINJAUAN YURIDIS KEBIJAKAN PEMERINTAH KABUPATEN JEMBER TERHADAP EKSPLOITASI GUMUK - Isnania Citra Saisabela, ICS; Isnania Citra Saisabela, ICS; Fauziyah Fauziyah, FA (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
In the use of hills in Jember District related land rights, which most hills in Jember District is private property rights and its utilization cannot be contrary with national interests. In the article 6 UUPA : " All rights over land have a social function". Then on the basis of the law of the government Jember could not only dwell  alone  without  a  policy  on  the  protection  of  the  hills. With  private ownership over the hills cannot be a reason to ignore the sustainability and environmental protection. The process of development and the protection of environment must be in harmony. Not mutual clashing that culminated in the destruction of the environment. The harmony between the use and maintenance of the environment related to the hills should always maintained in order to safeguard environment quality of life as well as the use of hills must be adjusted with the case and th nature of the right to useful both for peace and prosperity that does and useful for the society, state and public interests.